2017
DOI: 10.1111/php.12815
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Hydrogen Peroxide Highlights Gymnodinium catenatum (Dinophyceae) Sensitivity to Geomagnetic Activity

Abstract: The chain-forming dinoflagellate Gymnodinium catenatum was exposed to hydrogen peroxide. Microscopical examination revealed striking dose-response alterations in chain formation above 245 lM: singlets replaced the dominance of long chain formations. These observations were valid for cells acclimated to halogen light. Under fluorescent light, cells were more resistant to modifications in chain length after H 2 O 2 exposure. Growth along 9 h in the presence of extracellular H 2 O 2 followed an hormesis response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Exposure to FFA and H 2 O 2 in our experiments also produced changes in chain formation of G. catenatum, in which the decrease in cell density often coincided with an increase in single cell proportions. A similar response was also reported in the experiments by Vale (2018), in which concentrations above 245 mM of H 2 O 2 under halogen light caused single cells to dominate in cultures of G. catenatum. It has been suggested that high irradiance conditions can enhance the toxicity of H 2 O 2 in consequence to an increase in its transformation into hydroxyl radical (OH) (Drabkováet al, 2007).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Exposure to FFA and H 2 O 2 in our experiments also produced changes in chain formation of G. catenatum, in which the decrease in cell density often coincided with an increase in single cell proportions. A similar response was also reported in the experiments by Vale (2018), in which concentrations above 245 mM of H 2 O 2 under halogen light caused single cells to dominate in cultures of G. catenatum. It has been suggested that high irradiance conditions can enhance the toxicity of H 2 O 2 in consequence to an increase in its transformation into hydroxyl radical (OH) (Drabkováet al, 2007).…”
Section: Discussionsupporting
confidence: 86%
“…Chain formation in dinoflagellates such as G. catenatum may constitute a survival strategy by enhancing motility and allowing displacement of cells (Doblin et al, 2006) out of the reach of allelochemicals in the marine environment; however, this strategy may be limited by the spatial restrictions of laboratory cultures. While being stressed, naked dinoflagellates could employ alternative defense mechanisms facing allelopathy, including chain formation or separation (Vale, 2018;Shang et al, 2021;Fernańdez-Herrera et al, 2022). Due to the spatial constraints of the experimental setup, the strategy of chain cell formation of G. catenatum as a means of escape to allelochemicals was not clearly observed in the presence of FFA and H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has in common a chain-forming habit and production of the same PSTs: C1+2 (N-sulfocarbamoyl Gonyautoxins 2 + 3) and B1/GTX5 (Gonyautoxin 5). These studies revealed differential responses to shock, such as hypo-osmotic shock or addition of oxidizing agents (hydrogen peroxide), depending on the occurring SA and/or GMA at the time of the experiments (Vale, 2017a(Vale, , 2017b(Vale, , 2018a(Vale, , 2018b. The response to space weather (SPW) followed the hormetic dose-response model on numerous occasions (reviewed in Vale, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these molecules can have an antioxidant role as well (Dunlap and Yamamoto, 1995). MAAs that are more prone to oxidation (presenting double bonds) were more reduced than those less susceptible, highlighting that an ELFMF can act by increasing cellular oxidative stress status (Vale, 2018a(Vale, , 2018b(Vale, , 2020a. This was an expectable result, according to the best explanation for the interaction of weak magnetic fi elds that is postulated to occur through the radical-pair mechanism, increasing oxidative stress (Barnes and Greenbaun, 2015;Binhi and Rubin, 2022).…”
Section: Introductionmentioning
confidence: 99%